Analyzing the Relationship between Natural Resources Rents and Nepal’s Gross Domestic Product - Dangal, Dil Nath; Chapagai, Shiva Dutta; Ghimire, Krishna Prasad (Economic Review of Nepal, 2021)
The objective of this study is to analyze the relationship between natural resources rents and Gross Domestic Product (GDP), using the descriptive research design. The study collected quantitative data from the World Bank, covering the period from 1970 to 2020. Upon analyzing the relationship between gross domestic product (GDP) and total natural resources rents to GDP, the study found a statistically significant negative Pearson's correlation of -0.423 and a highly significant negative Spearman's rho correlation of -0.849. These findings indicate that there was a complex relationship between GDP and natural resources rents. The study suggests negative association between GDP and natural resource rents, providing insights into the importance of efficient use of natural resources in promoting sustainable economic growth.